(untitled) (CIPEEX, 2025)
Digital electoral advertising plays a pivotal role in the Brazilian democratic process by shaping communication between candidates and voters in the digital age. Social media platforms have transformed the dynamics of electoral campaigns, enabling more direct and interactive engagement, while simultaneously generating challenges such as the proliferation of disinformation and the misuse of personal data. The spread of fake news, amplified in the online environment, undermines the integrity of elections and produces legal implications in electoral, civil, and criminal domains. Although the Electoral Justice has advanced in regulating and supervising digital campaigning, it still struggles with the speed of online interactions and the absence of comprehensive legislation tailored to the digital reality. This study seeks to analyze the legal boundaries of electoral advertising in the digital era and the regulatory strategies designed to prevent abuses, thereby safeguarding popular sovereignty and fundamental rights. The research employed a qualitative and exploratory approach, based on bibliographic and documentary review, including academic studies, case law, and applicable legislation. Findings reveal that while social media has democratized political communication, it has also exacerbated risks of manipulation through disinformation and data misuse. Despite the efforts of the Electoral Justice, the lack of a modern and cohesive legal framework leaves significant gaps that compromise transparency and fairness in electoral disputes. Consequently, it is imperative to establish effective mechanisms that ensure the integrity of the democratic process by integrating legal modernization, institutional oversight, and civic awareness, while preserving transparency, accountability, and freedom of expression.